Sistem Informasi Manajemen dan Monitoring (Simamo) Rental Mobil Berbasis Iot (Sub Sistem Manajemen) - Widya Bintari; Muhammad Imam Ghozali; Wibowo Harry Sugiharto (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
Car rental is a business that provides car rental services to parties in need, both individuals and companies, usually ranging from a few hours to a few days. However, many car rental service providers experience several problems, such as a lack of vehicle monitoring, difficulty for renters to obtain information on car availability and data archives that are still conventional. The research method used was the waterfall system development method with UML system modeling. The programming language used is the PHP programming language and MySQL as the database. The system built has been tested using blackbox testing and whitebox testing and can run well. The features contained in the IoT-based car rental management and monitoring information system are car ordering, monitoring, managing car data and managing transactions. The aim of creating an IoT-based car rental management and monitoring information system is expected to be able to help renters and car rental providers in business processes.